Investigation of Flow Forming Process and Heat Treatment Effects on 2024 Aluminium Tubes - YALÇINKAYA, SENAİ (Springer Science and Business Media Deutschland GmbH, 2021)
The aim of this study is to investigate mechanical and microstructural properties of 2024 aluminium tubes (2024 AA) which are produced by flow forming technique and make comparisons between the flow formed 2024 AA, full annealed (2024-O) and solution heat treated then artificially aged (2024-T6) temper aluminium tubes. For this purpose, 70% reduction rate was applied on the 2024-O tempered samples by the flow forming process. The 2024-T6 samples demonstrated higher mechanical properties than 70% thickness reduced 2024 AA due to formation of Al2Cu precipitation. However, it was found that the mechanical properties of the flow formed 2024 AA was almost two times higher than that of the 2024-O sample. Furthermore, grain orientations of these three samples were investigated by the optical microscope. Although any grain orientations were not seen in 2024-O and 2024-T6 aluminum samples, severely grain orientations were observed after the flow forming process. © 2021, Springer Nature Singapore Pte Ltd.
Keywords: 2024 aluminum alloy; Cold working; Flow forming; Hardness; Microstructure; Reduction rate; Tensile test